A high activity Al–Bi@C for hydrogen generation from Al-water reaction. Issue 20 (15th October 2021) - Liao, Lumin; Guo, Xiaolei; Xu, Fen; Sun, Lixian; Wang, Tao; Zhou, Tianhao; Li, Yaying; Li, Jing; Zhang, Kexiang; Li, Bin; Peng, Hongliang; Zou, Yongjin; et al.
Abstract: A high activity carbon-loaded Bi (Bi@C) is synthesized by carbonizing a home-made Bi metal coordination compound. The results show that Bi@C effectively catalyzes the Al–H2 O reaction. Al–Bi@C composites are prepared by ball milling (named as Al–Bi@Cmilled ) or ball milling and spark plasma sintering (SPS) (named as Al–Bi@CSPS ). It can be found that the Al–Bi@CSPS obtained by sintered Al–Bi@Cmilled is converted from a powder to a block, which is beneficial for its practical application. Furthermore, the hydrogen generation performance of Al–Bi@CSPS is superior to that of Al–Bi@Cmilled . Such as the hydrogen yield of Al-5 wt% Bi@CSPS is higher than that of Al-5 wt% Bi@Cmilled (1292.0 mL g −1 vs 463.8 mL g −1 ), and Al-5 wt% Bi@CSPS also exhibits an excellent antioxidant ability. These results demonstrate that the SPS process is beneficial. The improvement mechanism of SPS on Al–Bi@C composites is studied by XRD, Raman spectroscopy, SEM-EDS and TEM. The fabricated Al–Bi@CSPS is expected to have practical application in the field of hydrogen supply.